2021
DOI: 10.1080/21655979.2020.1868733
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin induces apoptosis in prostate cancer cells via inactivation of the Keap1/Nrf2/ARE signaling pathway

Abstract: In this study, we examined the antitumor effects of Puerarin (PEU) on androgen-independent (DU145 and PC-3) and androgen-dependent (LNCaP) prostate cancer cells, and explored its potential mechanisms. Supplement with PEU (2.5 μM, 5 μM, and 10 μM) exhibited a marked inhibitory effect against the growth of DU145 and PC-3 cells, especially beyond 24 h, whereas there is only slight growth inhibitory effect on LNCaP cells at the high concentration of 10 μM at 72 h. This loss of cell viability in DU145 and PC-3 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…EdU staining assay was conducted according to a previous study [ 12 ]. After transfection, the cells were treated with 20 mmol/L of EdU working solution for 2 h. The cells were then fixed in 4% paraformaldehyde for 20 min at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…EdU staining assay was conducted according to a previous study [ 12 ]. After transfection, the cells were treated with 20 mmol/L of EdU working solution for 2 h. The cells were then fixed in 4% paraformaldehyde for 20 min at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, glutathione peroxidase 4 (GPX4) can inhibit peroxide under the action of glutathione (GSH), thereby inhibiting ferroptosis and promoting the growth of cancer cells [9,10]. An NRF2 signalling pathway is closely related to ferroptosis, and NRF2 can bind with antioxidant elements to activate downstream HO-1 to regulate iron and ROS [11][12][13][14][15]. Therefore, exploring the mechanism of gene regulation of NRF2/HO-1 pathway is necessary to inhibit ferroptosis-induced PRAD.…”
Section: Introductionmentioning
confidence: 99%
“…Puerarin has been reported to have a chemopreventive effect on colon cancer HT-29 cells by reducing cell viability, inducing apoptosis, activating Bax and caspase 3, and inhibiting c-Myc and Bcl-2 [ 21 ]. Another study indicated that the induction of androgen-independent prostate cancer cell apoptosis by puerarin is associated with the suppression of the Keap1/Nrf2/ARE signaling pathway, and puerarin pretreatment resulted in an increase in Keap1 and decline in Nrf2, HO-1, and NQO1 protein expression [ 22 ]. In the present study, for investigating the anticancer effect of puerarin on OC, we also focused on the role of apoptosis.…”
Section: Discussionmentioning
confidence: 99%